2014
DOI: 10.1016/j.midw.2013.07.016
|View full text |Cite
|
Sign up to set email alerts
|

The challenges facing midwifery educators in sustaining a future education workforce

Abstract: 283 wordsBackground:National and international trends have identified concerns over the ability of health and social care workforces in meeting the needs of service users. Attention has increasingly been drawn to problems of recruiting and retaining professionals within higher education, however data in relation to the midwifery profession is scant. AimTo examine the perceptions and experiences of midwifery educators, in south-west England, about the challenges facing them sustaining the education workforce of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 20 publications
1
7
0
2
Order By: Relevance
“…In fact, 93% of the participants reported that the resources of manpower are inadequate compared to the increasing number of nursing students rolling each year. These results are identical to those reported in (Agbedia, 2012;Albarran & Rosser, 2014;Bell et al, 2013;Budgen & Gamroth, 2008;Croxon & Maginnis, 2009;GormIey, 2003;Herrman, 2008 ;Luhanga, Billay, Grundy, Myrick, & Yonge, 2010;Mason, Shuman, & Cook, 2013;Norman, Buerhaus, Donelan, McCloskey, & Dittus, 2005;O'Flaherty & Phillips, 2015;Saarikoski, Isoaho, Warne, & Leino-Kilpi, 2008;Sarmiento, Laschinger, & Iwasiw, 2004;Sedgwick & Harris, 2012).…”
Section: Discussionsupporting
confidence: 90%
“…In fact, 93% of the participants reported that the resources of manpower are inadequate compared to the increasing number of nursing students rolling each year. These results are identical to those reported in (Agbedia, 2012;Albarran & Rosser, 2014;Bell et al, 2013;Budgen & Gamroth, 2008;Croxon & Maginnis, 2009;GormIey, 2003;Herrman, 2008 ;Luhanga, Billay, Grundy, Myrick, & Yonge, 2010;Mason, Shuman, & Cook, 2013;Norman, Buerhaus, Donelan, McCloskey, & Dittus, 2005;O'Flaherty & Phillips, 2015;Saarikoski, Isoaho, Warne, & Leino-Kilpi, 2008;Sarmiento, Laschinger, & Iwasiw, 2004;Sedgwick & Harris, 2012).…”
Section: Discussionsupporting
confidence: 90%
“…According to the literature, the main challenges of clinical midwifery training have been incompetent professors, limited opportunities to acquire the required skills, and lack of facilities and equipment (38,39). Successful implementation of curricula calls for the presence of quali ed and skilled professors (40). The results of a systematic review showed that the need to update the knowledge and skills of instructors in clinical practice is essential (41).…”
Section: Discussionmentioning
confidence: 99%
“…In Europe, and Norway, evidence suggests that nursing and midwifery educators are increasingly required to be in the possession of a doctoral degree for appointment as a lecturer [4, 33]. Once in education, midwifery educators are expected to meet higher education institutions’ expectations as researchers and develop pedagogical expertise [34].…”
Section: Discussionmentioning
confidence: 99%
“…Once in education, midwifery educators are expected to meet higher education institutions’ expectations as researchers and develop pedagogical expertise [34]. Thus, midwifery educators are stimulated to become academic scholars while practical skill instruction appears to be less valued [33]. In contrast to the ICM recommended standards, midwifery educators in Norway are not obliged to maintain competence in midwifery clinical practice once they have been appointed at an educational institution [35].…”
Section: Discussionmentioning
confidence: 99%